Developmental Expression of the Outer Hair Cell Motor Prestin in the Mouse - Abe, Takahisa (2007)
The development of motor protein activity in the lateral membrane of the mouse outer hair cell (OHC) from postnatal day 5 (P5) to P18 was investigated under whole-cell voltage clamp. Voltage-dependent, nonlinear capacitance (C(v)), which represents the conformational fluctuations of the motor molecule, progressively increased during development. At P12, the onset of hearing in the mouse, C(v) was about 70% of the mature level. C(v) saturated at P18 when hearing shows full maturation. On the other hand, C(lin), which represents the membrane area of the OHC, showed a relatively small increase with development, reaching steady state at P10. This early maturation of linear capacitance is further supported by morphological estimates of surface area during development. These results, in light of recent prestin knockout experiments and our results with quantitative polymerase chain reaction, suggest that, rather than the incorporation of new motors into the lateral membrane after P10, molecular motors mature to augment nonlinear capacitance. Thus, current estimates of motor protein density based on charge movement may be exaggerated. A corresponding indicator of motor maturation, the motor’s operating voltage midpoint , V(pkcm), tended to shift to depolarized potentials during postnatal development, although it was unstable prior to P10. However, after P14, V(pkcm) reached a steady-state level near −67 mV, suggesting that intrinsic membrane tension or intracellular chloride, each of which can modulate V(pkcm), may mature at P14. These developmental data significantly alter our understanding of the cellular mechanisms that control cochlear amplification and provide a foundation for future analysis of genetic modifications of mouse auditory development.